Functions and mechanisms of RNA tailing by nucleotidyl transferase proteins in plants - Chen, Jiwei; Li, Xiaozhen; Dong, Xianxin; Wang, Xiaoyan (Frontiers in Plant Science, 2024)
The addition of non-templated nucleotides at the 3' terminus of RNA is a pervasive and evolutionarily conserved posttranscriptional modification in eukaryotes. Apart from canonical poly(A) polymerases (PAPs), which are responsible for catalyzing polyadenylation of messenger RNAs in the nucleus, a distinct group of non-canonical PAPs (ncPAPs), also known as nucleotidyl transferase proteins (NTPs), mediate the addition of uridine and adenosine or of more intricate combinations of nucleotides. Among these, HEN1 SUPPRESSOR 1 (HESO1) and UTP: RNA URIDYLYLTRANSFERASE (URT1) are the two most extensively studied NTPs responsible for the addition of uridine to the 3' ends of RNAs (RNA uridylation). Recent discoveries have improved our understanding of the functions and mechanisms of uridylation mediated by HESO1 and URT1 in RNA metabolism. Furthermore, more NTPs have been identified to function in the 3' tailing of RNA and not solely through uridylation. Accumulating evidence indicates that RNA tailing plays important roles in plant growth and development, stress responses, and disease resistance. In this review, we examined the latest developments in RNA tailing by NTPs, with a focus on RNA uridylation and metabolism in plants. We also discussed the essential aspects for future research in this field.